Early modern concepts for a late modern world : Althusius on community and federalism - Hueglin, Thomas O. (Wilfrid Laurier University Press, 1999)
Johannes Althusius (1557-1638) was a political theorist and a combative city politician who defended the rights of small communities against territorial absolutism. He designed a system of politics in which sovereignty would be shared and jointly exercised by a plurality of collectivities, spatial as well as social, on the basis of mutual consent and social solidarity. Early Modern Concepts for a Late Modern World places Althusius in the context of his times and explains the main features of his political thought. It also suggests, perhaps most significantly, why his theories continue to resonate today. Hueglin's use of sources is thorough and scrupulous and provides a new interpretation of Althusius' theory.